The state-dependent effectiveness of hiring subsidies - Graves, Sebastian (American Economic Journal: Macroeconomics)
The responsiveness of job creation to shocks is procyclical, while the responsiveness of job destruction is countercyclical. This new finding can be explained by a heterogeneous-firm model in which hiring costs lead to lumpy employment adjustment. The model predicts that policies that aim to stimulate employment by encouraging job creation, such as hiring subsidies, are significantly less effective in recessions: these are times when few firms are near their hiring thresholds and many firms are near their firing thresholds. Policies that target the job destruction margin, such as employment protection subsidies, are particularly effective at such times.- Reproduced